Analysis and systematization of marketing studies data of the Ukrainian nanopowder market and formation of the program for its development - Malyshev, Victor; Kushchevska, Nina; Korotieieva, Antonina; Bruskova, Diana-Maria; Zalubovskiy, Mark; Lukashenko, Tetiana (Technology audit and production reserves, 2018)
The object of research is the Ukrainian market of nanopowders. Available literature sources do not cover this topic completely. Their data systematization will solve this problem. Therefore, in the paper the literature on the development of the Ukrainian nanotechnology industry is systematized, and the forecast of the period of release of certain nanomaterials to the market is made. The directions of R&D projects in this area are also analyzed, and a valuation of the production of nanomaterials is made. The literature sources analysis made it possible to note launch and implementation of targeted programs for nanostructured materials and nanotechnology in all leading countries around the world. The indexes and development trends of the modern Ukrainian nanotechnology branch are presented. Ukrainian nanotechnologies market is at the initial stage of its formation. The total amount of investments in nanotechnology projects is dominated by state funding. Today, Ukraine is far behind the developed countries by the volume of private investments in researches in the field of nanotechnology. The commercial nanopowders market in Ukraine is practically not developed. The country is just beginning to introduce nanosized products standards and enterprises certification. The studies of Ukrainian companies in the field of nanotechnologies are aimed at modifying various materials. The terms for the nanopowders release to the commercial market depending on application sectors are proposed. The distribution of Ukrainian enterprises by nanotechnology research fields is presented together with the projects structure depending on the research fields in the nanotechnology area. Costs analysis of the Ukrainian nanopowders market is carried out. It is shown that high costs of nanopowders are due to both low production volume and high costs of raw materials. The main branches-consumers of nanoproducts in Ukraine are presented, and forecasts for market development up to 2025 are made. Due to the analysis and systematization of literature data of scientists at the Ukrainian market of nanopowders and the consideration of its development programs it becomes possible to obtain objective information on the Ukrainian market of nanopowders and to predict its future development.